2020
DOI: 10.3389/fped.2020.00210
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal Surfactant Combined With Budesonide for Neonatal ARDS

Abstract: Acute respiratory distress syndrome (ARDS) is a clinical condition characterized by acute diffuse inflammatory lung injury and severe hypoxemia. In 2017, the Montreux Consensus defined diagnostic criteria for ARDS in the neonatal period. The management of ARDS includes strict adherence to lung-protective ventilation strategies and therapeutic agents to improve gas exchange. We report two similar cases of premature infants with gestational ages of 23 and 24 weeks diagnosed with neonatal ARDS according to the Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…While these molecules have not yet reached clinical use, it is not surprising that budesonide, a well-known synthetic steroid, had been administered using surfactant as carrier. This gave promising results in neonates with NARDS [ 90 ]. Also, budesonide decreases the expression of secretory phospholipase A2 [ 91 ] and has a clinically significant anti-inflammatory effect in preterm neonates at risk of broncho-pulmonary dysplasia [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…While these molecules have not yet reached clinical use, it is not surprising that budesonide, a well-known synthetic steroid, had been administered using surfactant as carrier. This gave promising results in neonates with NARDS [ 90 ]. Also, budesonide decreases the expression of secretory phospholipase A2 [ 91 ] and has a clinically significant anti-inflammatory effect in preterm neonates at risk of broncho-pulmonary dysplasia [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 has been associated with acute respiratory distress syndrome (ARDS), especially in severely ill patients [ 24 ]. Interestingly, some studies have investigated corticosteroids in the context of ARDS [ 25 , 26 ]. Mohamed and Meguid found that budesonide improved lung mechanics and oxygenation when patients with ARDS were nebulized with budesonide.…”
Section: Discussionmentioning
confidence: 99%
“…The use of surfactant as a vehicle to deliver steroids to the lungs of premature infants has been the subject of increasing clinical interest. 20 Several clinical studies have investigated the efficacy of this steroid delivery mode in preventing BPD 32 and chronic respiratory diseases 33 or in treating neonatal ARDS 34,35 in premature infants. Two recent meta-analysis studies reported that intratracheal instillation of steroid-surfactant combination was an effective therapy for preventing BPD in preterm infants with neonatal ARDS, but its benefit in reducing mortality was inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] In animal studies, this steroid delivery mode has been used to investigate its efficacy in reducing ALI in animal models of surfactant-depleted lung diseases, 23,25 MAS, 26 hyperoxia 27 , and injurious mechanical ventilation. 28,29 In clinical studies, this steroid delivery mode has been used to prevent BPD [30][31][32] and chronic diseases 33 or to treat neonatal ARDS 34,35 in premature infants. However, no study has been conducted to investigate the therapeutic effect of this steroid delivery approach on LPS-induced ALI in surfactant-insufficiency lungs.…”
mentioning
confidence: 99%